A atividade minerária e a dinâmica demográfica/econômica em Conceição do Mato Dentro (MG) - Mariana Sena Lara (2015)
The history of the city of Conceição do Mato Dentro (CMD) is similar to the reality of many other mining cities at Minas Gerais. Gold mining was the most prominent in the XVIII century. Nowadays the city is the center of investments in a region where the economy is based on iron ore exploitation and ecological tourism. There are controversies and issues on the role of mining in the development of the regions where it occurs: do mining economies have more disadvantages than advantages to conduct economic or social development processes? Do they limit other productive sectors' capacity to expand? Is it a propelling factor of development? Taking aside controversies, it is a fact that mining ventures causes both positive and negative impact on the cities and regions where they set up, such as the elevation of the migration rate. The studies about migration in Brazil tend to analyze the process at a state level, with low frequency of studies at a city level. However, the reality in which the migrates weight up their choices appeals mainly to the inherent aspects of the local scale. In that sense, the main object of this essay is to evaluate the possible impacts resulting from the mining activity in the migratory dynamics of CMD. It includes the identification of associated/occupational and environment conditions of the local population, either migrant or not. The results enabled identify direct and indirect effects deriving of the mining activity in CMD, even in its embryonic stage. Even though the flows volume isnt very expressive, taking into account the population size living in the city, a significant increase in immigration can be observed in the last decade. Considering the sector analyzed by the census, its also noted the positive distinction in the social and environment conditions of the recent migrants that showed high occupational link with the mineral sector.